The Influence of Principal Leadership, Decision Making Communication Systems and Work Motivation on Teacher Job Satisfaction at UPT SPF SDN Tamamaung 1 Makassar - Basora, Basora; Yunus, Muh; Yahya, Muh (CV. Rayyan Dwi Bharata, 2025)
This research aims to analyze and examine 1) Principal Leadership, Decision Making Communication Systems and Work Motivation simultaneously influence teacher job satisfaction at UPT SPF SDN Tamamaung 1 Makassar. 2) The leadership of the principal partially influences teacher job satisfaction at UPT SPF SDN Tamamaung 1 Makassar. 3) The communication system influences teacher job satisfaction at UPT SPF SDN Tamamaung 1 Makassar. 4) Decision making influences teacher job satisfaction at UPT SPF SDN Tamamaung 1 Makassar. 5) Work Motivation influences teacher job satisfaction at UPT SPF SDN Tamamaung 1 Makassar. This type of research is quantitative research. The population of this study were all class V teachers at UPT SPF SDN Tamamaung 1 Makassar with a total of 17 people, the sample taken was the entire population. The data collection technique uses research questionnaires and documentation, while the data analysis technique uses descriptive analysis and t test. The results of the research show that 1) Principal Leadership, Decision Making Communication Systems and Work Motivation simultaneously influence teacher job satisfaction at UPT SPF SDN Tamamaung 1 Makassar. research findings show that there is a direct influence of Fcount Ftable (37.063 3.09), so Ha is accepted and H0 is rejected, meaning that there is a significant influence simultaneously between the variables Principal Leadership (X1), Communication System (X2), Decision Making (X3) and Teacher Work Motivation (X4) on teacher job satisfaction at UPT SPF SDN Tamamaung 1, 2) Principal leadership partially influences teacher job satisfaction at UPT SPF SDN Tamamaung 1 Makassar. obtained tcount ttable, namely 4.3051.660 and sig 0.000.05. It can be explained that there is a direct influence of the Principal's Leadership on the Job Satisfaction of teachers at UPT SPF SDN Tamamaung 1, 3) The Communication System influences teacher job satisfaction at UPT SPF SDN Tamamaung 1 Makassar. obtained tcountttable, namely 4.9581.660 and sig 0.0000.05. It can be explained that there is an influence of the Communication system on teacher job satisfaction at UPT SPF SDN Tamamaung 1, 4) Decision making influences teacher job satisfaction at UPT SPF SDN Tamamaung 1 Makassar. obtained tcountttable, namely 4.0441.660 and sig 0.0000.05. It can be explained that there is a direct influence on decision making on teacher job satisfaction at UPT SPF SDN Tamamaung 1, 5) Work Motivation influences teacher job satisfaction at UPT SPF SDN Tamamaung 1 Makassar. obtained tcount ttable, namely 4.2031.660 and sig 0.0000.05. It can be explained that there is a direct influence. Work motivation has a direct influence on the job satisfaction of teachers at UPT SPF SDN Tamamaung 1.